2014
DOI: 10.1111/pan.12468
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a rapid bolus dose of dexmedetomidine (ED50) with acceptable hemodynamic outcomes in children

Abstract: The ED50 of dexmedetomidine administered over 5 s without significant hemodynamic compromise is 0.49 mcg·kg(-1). Further work is needed to determine the 'safe' (ED5 or less) and effective dose for desired perioperative clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…In this respect, the lack of adverse hemodynamic side effects reported by Kim et al are intriguing. They might be in line with recent reports on pediatric patients in whom a bolus injection was acceptable with hemodynamic responses [15]. …”
supporting
confidence: 90%
“…In this respect, the lack of adverse hemodynamic side effects reported by Kim et al are intriguing. They might be in line with recent reports on pediatric patients in whom a bolus injection was acceptable with hemodynamic responses [15]. …”
supporting
confidence: 90%
“…Conversely, hypertension and bradycardia have ensued after rapid intravenous boluses of dexmedetomidine, followed by vasodilation and moderate hypotension. [23][24][25] Dexmedetomidine is also known to inhibit sinoatrial and atrioventricular node function, which can lead to bradycardia, especially in children with rhythm disturbances. 26,27 While speculative, use of a drug that provides sedation by a distinctly different mechanism from that of traditional gamma-aminobutyric acid agonist or Nmethyl-D-aspartate antagonist sedatives and anesthetics could potentially avoid the neurocognitive abnormalities described following repeated exposures to these agents.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study,Dawes et al showed that 0.49 µg/kg can be used as a bolus over 5 seconds in children (age 5-9 years) without causing any significant hemodynamic compromise21 .The authors in this study used 0.5 µg/kg loading dose (in 2 divided doses) over 30 seconds, alternating with ketamine. In this way, both the groups received induction bolus over 30 seconds.In the present study, all of the cases were completed successfully, and there was no episode of hypoapnea or desaturation in the group DK.…”
mentioning
confidence: 86%